Non-contact piezoelectric rotary motor modulated by giant electrorheological fluid - Qiu, Wei ; 0000-0003-3032-4172; Hong, Yaying; Mizuno, Yosuke; Wen, Weijia; Nakamura, Kentaro (Sensors and Actuators, A: Physical, 2014)
A bidirectional non-contact rotary motor using a piezoelectric torsional vibrator and the giant electrorheological (GER) fluid is described in this paper. By applying the dynamic electric signal with a square waveform to the GER fluid, which is in phase with the vibration velocity of the torsional vibrator, bidirectional rotation at an excitation frequency of 118 Hz is achieved. This motor generates 1.04 mN m torque when the electric field strength of 2 kV/mm with 30% duty cycle is applied to the GER fluid, and the rotational speed of up to 7.14 rad/s is achieved if the electric field strength is increased to 2.5 kV/mm. Similarities and differences of the motor characteristics between this motor and the conventional standing wave ultrasonic motors are discussed. The motor performance is not ideal under high electric field strength, indicating that the response time of the GER fluid is dependent on the electric field strength.
Keywords: Non-contact ultrasonic motor; Giant electrorheological fluids; Torsional vibrator